The familiars - Halls, Stacey (Leicestershire; ISIS, 2020)
County of Lancaster, 1612: Fleetwood Shuttleworth is seventeen years old, married, and pregnant for the fourth time. But as mistress of Gawthorpe Hall, she still has no living child, and her husband Richard is anxious for an heir. When Fleetwood finds a letter that she isn't suppose to read from the doctor who delivered her third stillbirth, she is dealt the crushing blow that she will not survive another pregnancy. Then she crosses paths by chance with Alice Gray, a young midwife, who promises to help her give birth to a healthy baby and to proof the physician wrong. As Alice is drawn into the witchcraft accusations that are sweeping the north-west, Fleetwood risks everything by trying to help her. But there more to Alice than meets the eye?
Keywords: Female friendship$1 (BFictions